2012
DOI: 10.1007/s11010-012-1491-8
|View full text |Cite
|
Sign up to set email alerts
|

SASH1 regulates proliferation, apoptosis, and invasion of osteosarcoma cell

Abstract: SASH1, a member of the SLY-family of signal adapter proteins, is a candidate tumor suppressor in breast and colon cancer. The SASH1 protein possesses both the SH3 and SAM domains, indicating that it may play an important role in intracellular signal transduction. Reduced expression of SASH1 is closely related to tumor growth, invasion, metastasis, and poor prognosis. However, the biological role of SASH1 remains unknown in osteosarcoma. To unravel the function of SASH1, we explored the expression of SASH1 in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 22 publications
3
49
0
Order By: Relevance
“…6,7 Consistent with the onset of carcinoma in the affected individuals in this study, SASH1 was recently reported to be involved in the tumorigenesis of several cancers. [15][16][17][18][19][20] Cellular experiments showed that SASH1 localizes to the nucleus and cytoplasm of epithelial cells and might regulate cellular migration and adhesion, through its role in protruding membrane structures. 21 Through its central SH3 domain, SASH1 interacts with the actin cytoskeleton and especially cortactin, a major regulator of actin filament dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Consistent with the onset of carcinoma in the affected individuals in this study, SASH1 was recently reported to be involved in the tumorigenesis of several cancers. [15][16][17][18][19][20] Cellular experiments showed that SASH1 localizes to the nucleus and cytoplasm of epithelial cells and might regulate cellular migration and adhesion, through its role in protruding membrane structures. 21 Through its central SH3 domain, SASH1 interacts with the actin cytoskeleton and especially cortactin, a major regulator of actin filament dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…SASH1 encodes a candidate tumor suppressor from the SLY family of signal proteins. [15][16][17][18][19][20] This variant was absent from Exome Variant Server, dbSNP and local exomes, predicted as deleterious by Condel and possibly damaging by Polyphen2, and comes from a well-conserved sequence (GERP conservation score: 5090) (see Web Resources). Cosegregation analysis in all available relatives confirmed its presence in a homozygous state in both affected patients (III.6 and III.3), in a heterozygous state in both parents and an unaffected brother (III7) and absent in the unaffected sister (III4).…”
Section: Genetic Investigationsmentioning
confidence: 99%
“…In a recent study, exogenous overexpression of the MT1F gene increased apoptosis in colon cancer cells [37], which supports our data. SASH1, a potential tumor suppressor, may function in various signaling pathways due to its SH3 and SAM domains; thus, its downregulation is related to tumor growth [38]. Therefore, its increased expression after hesperetin treatment might induce apoptosis and growth suppression.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that the down-regulation of SASH1 is at least in part due to gene deletion (13). Down-regulation of SASH1 expression was closely correlated with tumor invasion, metastasis, and poor prognosis (22)(23)(24). However, the specific role of SASH1 in ovarian carcinoma has not yet been reported in the literature.…”
Section: Introductionmentioning
confidence: 88%
“…Therefore, the study of suppressor genes and apoptosis-related genes in carcinogenesis and tumor progression in ovarian carcinoma has drawn increasing attention. A previous study indicated that SASH1 is a tumor suppressor gene, located on chromosome 6q24.3 (22). Zeller et al (13) demonstrated reduced or absent SASH1 expression in 6 breast cancer cell lines, which exhibit a chromosome 6q24.3 deletion.…”
Section: Introductionmentioning
confidence: 99%